2020
DOI: 10.1038/s41598-020-72848-0
|View full text |Cite
|
Sign up to set email alerts
|

A specialized reciprocal connectivity suggests a link between the mechanisms by which the superior colliculus and parabigeminal nucleus produce defensive behaviors in rodents

Abstract: The parabigeminal nucleus (PBG) is the mammalian homologue to the isthmic complex of other vertebrates. Optogenetic stimulation of the PBG induces freezing and escape in mice, a result thought to be caused by a PBG projection to the central nucleus of the amygdala. However, the isthmic complex, including the PBG, has been classically considered satellite nuclei of the Superior Colliculus (SC), which upon stimulation of its medial part also triggers fear and avoidance reactions. As the PBG-SC connectivity is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 82 publications
(179 reference statements)
6
27
0
Order By: Relevance
“…These neuronal responses are presumably subject to modulation as a looming stimulus can induce both rapid escape and freezing, depending on environmental context like the presence of a shelter (Vale et al, 2017) or stimulus parameters such as loom speed and size (Yang et al, 2020). A highly visual diurnal rodent, the com-mon degu (Octodon degus), also shows looming-evoked escape (Deichler et al, 2020). In mice, superficial layer neurons respond to visual looming (Zhao et al, 2014), and optogenetic inhibition of the excitatory SC neurons in the medial region of the intermediate layer reduces looming-induced freezing (Wei et al, 2015).…”
Section: Linking Superficial and Deep Layersmentioning
confidence: 99%
“…These neuronal responses are presumably subject to modulation as a looming stimulus can induce both rapid escape and freezing, depending on environmental context like the presence of a shelter (Vale et al, 2017) or stimulus parameters such as loom speed and size (Yang et al, 2020). A highly visual diurnal rodent, the com-mon degu (Octodon degus), also shows looming-evoked escape (Deichler et al, 2020). In mice, superficial layer neurons respond to visual looming (Zhao et al, 2014), and optogenetic inhibition of the excitatory SC neurons in the medial region of the intermediate layer reduces looming-induced freezing (Wei et al, 2015).…”
Section: Linking Superficial and Deep Layersmentioning
confidence: 99%
“…We found monosynaptic inputs from the PBG to the shell, but not from the PBG or PPT to the dLGN core, suggesting that neurons in the PBG provide inputs to neurons in the dLGN shell, but not to excitatory relay neurons in the dLGN core. The PBG has been reported to receive retinal inputs from ON–OFF DS‐GCs and alpha‐RGCs (Reinhard et al, 2019) and be involved in innate and visual defensive responses, such as escape and freezing (Deichler et al, 2020). We found that the shell dLGN receives inputs from the ipsilateral sSC and contralateral PBG.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is consistent with those of a study indicating that both the parabigemino‐genuculate projections and tecto‐genuculate projections to the dLGN terminate in the shell region containing W‐like cells (Harting, Van Lieshout, et al, 1991). The interactions between the SC, PBG, and dLGN might be important for visually guided avoidance behaviors (Deichler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not identify the source of this modulation in this study. Potential sources include local circuitry within the SC 21 , 28 , a pathway with higher latency such as a cortical pathway 29 , and/or reciprocal connections with other brain areas such as the parabigeminal nucleus [30][31][32] .…”
Section: Potential Sources Of Modulationmentioning
confidence: 99%